The Welsh Government Flying Start Data Linking Project - Herbert, Laura; Whiffen, Tony; Lowe, Sarah; Solomons, Craiger (International Journal of Population Data Science, 2019)
Background with rationale Flying Start is the Welsh Government’s (WG) flagship Early Years programme for families with children aged less than 4 years of age. Running since 2006, the four entitlements are: Enhanced Health Visiting Free part-time childcare for 2-3 year olds Parenting support Speech, language, and communication support Previous Flying Start evaluations have focused on area-based analysis to explore outcomes of Flying Start eligible children. The current project is the first to obtain individual level Flying Start data to look at outcomes around health, education and social care and to explore these outcomes in relation to levels of engagement with different entitlements of Flying Start. Main Aim The aim of the project is to link individual-level Flying Start intervention data with health, education and other data to investigate the potential impact of Flying Start. Methods/Approach Individual level data for Flying Start children is currently being obtained from six pilot Local Authorities in Wales using the Secure Anonymised Information Linkage (SAIL) databank. The Flying Start data will be linked to other data within the SAIL databank in order to investigate the impact of the Flying Start programme on a number of different outcomes including hospitalisations, Accident & Emergency (A&E) attendances, Primary Care interactions, educational attainment, school attendance and Special Educational Needs (SEN). Results The project will report on the emerging findings from the analysis of pilot data. It is anticipated that Flying Start dosage effects will also be investigated and reported on. Conclusion The findings will feed into the current evidence base for Flying Start and help to inform future policy-making. If successful, this model of evaluation is likely to be adopted by related WG programmes.